Capital structure of non-financial firms in Malaysia / Siti Noor Amirah Jusoh - Jusoh, Siti Noor Amirah (Faculty of Business Management, 2017)
This paper identifies a relationship between firm specific characteristics and capital structure of non-financial firms in Malaysia. Capital structure is one of the most important effective measures on the valuation and direction of economic enterprises in the capital markets. This paper purpose is to examine the relationship between capital structure towards firm size (FS), profitability (ROA), liquidity (CR), tangibility (TANG) and growth opportunities (GRW). The capital structure will be measured by total debt ratio. This study is using secondary data and panel data analysis. The data is obtained from annual report of listed non-financial company in Malaysia. The annual report will be obtained from Bursa Malaysia for six selected listed non-financial firms in Malaysia. The data is collected from 2006 to 2015. From this study, the expected finding of liquidity, profitability, and growth opportunities were found to have negative relationship on debt ratio, while firm size and tangibility were found to have positive relationship on debt ratio. However the result show in this study is different with expected finding which are liquidity, growth opportunities and tangibility show negative relationship with debt ratio, while firm size and profitability are positive related towards debt ratio. Keywords: Panel data, Pecking Order Theory